The Effects of Trenbolone Supplementation on The Extremity Bones in Running Rats - Ali Sarı; Sefa Lök (Türk Spor ve Egzersiz Dergisi)
ABSTRACTAnabolic steroids are testosterone derivatives through which anabolic effects are maintained and androgenic effects are minimized. The use of ergogenic agents is increasing among athletes for doping in order to increase physical performance and change external image. The objective of this study was to determine effects of trenbolone supplement administered on running rats for 4 weeks on extremity bones. The study was conducted with 28 male Wistar rats aged 28 days with a mean weight of 61,80 g supplied from the Selcuk University Experimental Medical Research and Application Center. The rate were divided into 4 groups as C (Controls), E (Exercise), T (Trenbolone), and TE (trenbolone + Exercise). The trial period lasted 4 weeks. Supply, care, feeding, and experimental applications of rats were performed in the Selcuk University Experimental Medical Research and Application Center. Anterior and posterior extremities’ bones were dissected and exposed, and the humerus and femur bones exposed were dried. Length, corpus thickness, cortex thickness, and medulla diameter points were determined and the necessary measures were taken. The results are expressed as mean ± SD. ANOVA and Duncan tests were used for the comparison of data. p lt;0.05 values were considered statistically significant. The mean femoral length was found as 31.31 ± 0.69 in the rats in Group T, 31.46±0.72 in Group E, 31.51±0.58 in Group TE, and 31.48 ± 0.71 in Group C (controls). Examining the mean femoral lengths of Groups T, E, TE and C; the mean femoral length in Group T was numerically higher than that of the Groups E, TE and C, although the difference was not statistically significant (F:0.112; p:0.637). The mean humerus length was found as 24.93 ± 0.59 in the rats in Group T, 24.96±0.68 in Group E, 25.33±0.81 in Group TE, and 25.29±0.77 in Group C (controls). Examining the mean humerus lengths of Groups T, E, TE and C; the mean humerus length in Group T was numerically higher than that of the Groups E, TE and C, although the difference was not statistically significant (F:0.608; p:0.355). We found that the mean values of corpus and cortex thickness, and medullary diameters were similar in the Groups T, E, TE, and C, and the differences were not statistically significant (p gt;0.05). Results of this study indicate that trenbolone supplement may lead to early epiphyseal closure in femur and humerus bones of rats, ceasing the increase in their length. We believe that the results obtained from this trenbolone trial will provide important data to the studies that will be conducted on anabolic androgenic steroids.